PETA KULTURAL MADURA INTERAKTIF DALAM PEMBELAJARAN PKN DI SDN PARSANGA II - Muhammad Romli; I Nengah Suastika; Dewa Bagus Sanjaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a contextual and local wisdom-based interactive learning media called the Madura Cultural Map to improve Civic Education (PKn) learning outcomes for third-grade students at SDN Parsanga II, Sumenep Regency. The method used is Research and Development (R&D) employing a modified Borg & Gall model, which includes the stages of needs analysis, design, expert validation, limited trial, revision, and broader field testing. The media features representations of distinctive Madurese culture such as karapan sapi (bull racing), batik, saronen music, and fishing traditions—presented in an interactive format that combines visuals, narrative text, and audio. Expert validation on content and media aspects indicated that the product was in the "appropriate" category for use. Trials with 85 students showed a 92% engagement rate, 88% comprehension level, and 85% effectiveness in supporting the learning process. These findings indicate that the Madura Cultural Map interactive media is effective in enhancing conceptual understanding of citizenship, shaping students’ character, and fostering appreciation for local culture. Therefore, this media can serve as an innovative alternative for culturally rooted, enjoyable, and contextual Civic Education that supports the holistic development of student competencies.